Got "critical minerals"? Hooray! But be careful! - Louis T. Wells (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
When a country has "critical minerals," certain issues require special attention in the country's mining legislation or while negotiating contracts with potential mining investors. As well, to obtain maximum benefit the government should prepare for negotiations with investors' home governments, which have strategic interests in these minerals.
Keywords: 330